2012
DOI: 10.1080/00224499.2011.568126
|View full text |Cite
|
Sign up to set email alerts
|

“The Young Ones are the Condom Generation”: Condom Use amongst Out-of-School Adolescents in Rural Southwest Uganda

Abstract: This article reports on factors influencing condom use among out-of-school adolescents in rural southwest Uganda. Despite an abundance of negative discourses and myths about condoms in the community, these adolescents believe condoms protect them from sexually transmitted infections, HIV, and premarital pregnancies. Girls want partners to use condoms, but most lack the confidence to insist. Girls aged 13 to 14 reported the least difficulty asking for condoms; older girls attributed this to coming-of-age in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…For instance, the conspiracy theory that HIV was created in an American laboratory targeted at reducing the African population and was delivered to Africans through the polio vaccine affected uptake of polio and other vaccines, especially when they were donated from the west [40]. Similarly, rumours that donated condoms were tainted with HIV affected condom use [22]. These and other conspiracy theories have been reported as influencing decision-making for some parents;

“Remember this is a white man’s vaccine.

…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the conspiracy theory that HIV was created in an American laboratory targeted at reducing the African population and was delivered to Africans through the polio vaccine affected uptake of polio and other vaccines, especially when they were donated from the west [40]. Similarly, rumours that donated condoms were tainted with HIV affected condom use [22]. These and other conspiracy theories have been reported as influencing decision-making for some parents;

“Remember this is a white man’s vaccine.

…”
Section: Resultsmentioning
confidence: 99%
“…A study by Marlow et al [1] found that mothers who thought their partners would be favourable to vaccination were likely to accept vaccination for their daughters. The male presence within the family unit is typically one of authority, thus a father holds the greater power in the decision-making process in all matters including sexuality, reproduction and matters pertaining to the children [22]. This is of particular importance in the African context, where the man in any relationship is the decision maker [22], making it impossible for mothers to act without permission from their husbands [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One combined school and community [45] and the other combined clinic and households [49]. Also, two articles focused on only females [40,42] whilst one focused on only male [38] and the remaining eighteen considered both gender.…”
Section: Selected Studiesmentioning
confidence: 99%
“…In addition, eleven of the studies focused on barriers to SRH services [32,[36][37][38][39][40]42,44,46,48,50], three on SRH education [33, 34,38]; another three on acceptance of SRH services [43,47,51], two on SRH services preferences [11,31], and one each on satisfaction from SRH services [35] and SRH services utilization [41].…”
Section: Selected Studiesmentioning
confidence: 99%